Serangan Aktivis Dalam Perspektif Dampak Dan Tantangan Penegakan Hukum - Wahyono, Dodik; Mangar, Irma; Tifani Akmalu Syifa (Diktum: Jurnal Ilmu Hukum, 2026)
This study aims to analyze the form and characteristics of activist attacks from a legal perspective and examine the challenges in law enforcement against this phenomenon and efforts to counter it. Activism as part of freedom of expression has an important role in democratic life, but in practice it often develops into actions that go beyond the limits of the law, both in the form of physical, verbal, and digital attacks. This situation creates a dilemma between the protection of human rights and the need to maintain order and legal certainty. This research uses normative legal research methods with legislative and conceptual approaches. The data used is in the form of secondary data consisting of primary, secondary, and tertiary legal materials, which are collected through literature studies and analyzed qualitatively by descriptive-analytical methods. The results of the study show that activist attacks have a collective, confrontational characteristic, and are often influenced by specific ideological interests. The impact not only disrupts public order, but also creates legal uncertainty due to the unclear boundaries between freedom of expression and lawlessness. Law enforcement against this phenomenon faces various challenges, including unclear regulations, limited capacity of law enforcement officials, political pressure, public resistance, and cross-jurisdictional development of digital technology